2004
DOI: 10.1073/pnas.0401489101
|View full text |Cite
|
Sign up to set email alerts
|

Consistency of a counterexample to Naimark's problem

Abstract: We construct a C*-algebra that has only one irreducible representation up to unitary equivalence but is not isomorphic to the algebra of compact operators on any Hilbert space. This answers an old question of Naimark. Our construction uses a combinatorial statement called the diamond principle, which is known to be consistent with but not provable from the standard axioms of set theory (assuming that these axioms are consistent). We prove that the statement ''there exists a counterexample to Naimark's problem … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
56
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 40 publications
(57 citation statements)
references
References 17 publications
1
56
0
Order By: Relevance
“…By Lemma 4 of ref. 6 there is a separable C*-algebra A ␣ ϩ 1 ʕ B(H) that contains A ␣ , a ␣ , and q ␣ , and such that the restriction f ␣ ϩ 1 of g to A ␣ ϩ 1 is pure. To see this, write B(H) as the union of a continuous nested transfinite sequence of separable C*-algebras B ␥ such that B 0 is the C*-algebra generated by A ␣ , a ␣ , and q ␣ .…”
Section: (H)mentioning
confidence: 99%
“…By Lemma 4 of ref. 6 there is a separable C*-algebra A ␣ ϩ 1 ʕ B(H) that contains A ␣ , a ␣ , and q ␣ , and such that the restriction f ␣ ϩ 1 of g to A ␣ ϩ 1 is pure. To see this, write B(H) as the union of a continuous nested transfinite sequence of separable C*-algebras B ␥ such that B 0 is the C*-algebra generated by A ␣ , a ␣ , and q ␣ .…”
Section: (H)mentioning
confidence: 99%
“…Perhaps it is worth pointing out that in general, heroic attempts to get rid of separability hypotheses for problems in operator algebras can force one to look carefully at the fundamentals of set theory. For example, Akemann and Weaver [AW04] have constructed a counterexample to Naimark's problem by making use of a set-theoretic principle that is known to be consistent with, but not provable from, the standard axioms of set theory. They also showed that the statement There is a counterexample to Naimark's problem that is generated by ℵ 1 elements is undecidable within standard set theory.…”
Section: Pure States Of Smentioning
confidence: 99%
“…The additional axiom we add to Zermelo-Fraenkel set theory with the axiom of choice (ZFC) is Jensen's ♦ ℵ 1 , discussed below in section 3, and our construction is motivated by the work of Akemann and Weaver from ref. 6, where they use ♦ ℵ 1 to construct a counterexample to the Naimark problem. Our main theorem is: Theorem 1.1.…”
Section: Introductionmentioning
confidence: 99%